Effect of Adding Nano-Materials and Carbon Fiber on Impact Strength of Cementitious Composite (CC) - Raouf, Zain El-Abdin; Al-Suhaili, Rafia H.; Mahdi, Zainab H. (Al-Nahrain Journal for Engineering Sciences, 2017)
This study involves the addition of nano silica (NS) with average particle size 12nm, micro high reactivity mitakaaolin (MHRM) particle size ? 0.554 ? 1.271 µm, micro ground granulated blast-furnace slag (MGGBFS) particle size ? 0.365